Influence of boron on the properties of basic magnesium sulfate cement. (11th April 2022) - Zhang, Xiaoyuan; Zhang, Huifang; Wu, Chengyou
Highlights: The addition of boric acid has a great effect on the early strength of BMSCs. After calcination of boric acid at high temperature, magnesium borate is formed. Boron does not change the phase of BMSC, and the hydration product is still 517 phase. Boric acid plays a retarding role in BMS cement. Abstract: Magnesium hydroxide was calcined at different temperatures to prepare different active magnesia, and 3% and 5% B was added to the magnesia precursor to prepare basic magnesium sulfate cement (BMSC). The phase composition of the hydration products and the development of the pore structure were analysed to investigate the effect of the salt lake coexisting B impurity on the performance of BMSC. The results showed that the hydration rate of the BMSC prepared by adding B is slower, the setting and hardening times were longer, and the compressive strength was lower than those of the control group. Furthermore, B significantly affected the early compressive strength of the BMSC prepared using high-activity magnesium oxide. Mainly because the specific surface area of the magnesia calcined at a low temperature (700 °C) increased, the crystal grain size reduced, the degree of crystallinity reduced, and the number of internal defects increased. In the case of the magnesia obtained by calcining at a high temperature (1000 °C) and adding boric acid, a large number of rough magnesium borate complexes were formed on the surface, and the adjacent magnesium oxide continuously agglomerated and underwent sintering, which improved the degree of crystallinity and reduced the number of internal defects.